Suppression among alleles encoding nucleotide‐binding–leucine‐rich repeat resistance proteins interferes with resistance in F1 hybrid and allele‐pyramided wheat plants. (23rd July 2014) - Stirnweis, Daniel; Milani, Samira D.; Brunner, Susanne; Herren, Gerhard; Buchmann, Gabriele; Peditto, David; Jordan, Tina; Keller, Beat
Summary The development of high‐yielding varieties with broad‐spectrum durable disease resistance is the ultimate goal of crop breeding. In plants, immune receptors of the nucleotide‐binding–leucine‐rich repeat (NB‐LRR) class mediate race‐specific resistance against pathogen attack. When employed in agriculture this type of resistance is often rapidly overcome by newly adapted pathogen races. The stacking of different resistance genes or alleles in F1 hybrids or in pyramided lines is a promising strategy for achieving more durable resistance. Here, we identify a molecular mechanism which can negatively interfere with the allele‐pyramiding approach. We show that pairwise combinations of different alleles of the powdery mildew resistance gene Pm3 in F1 hybrids and stacked transgenic wheat lines can result in suppression of Pm3‐based resistance. This effect is independent of the genetic background and solely dependent on the Pm3 alleles. Suppression occurs at the post‐translational level, as levels of RNA and protein in the suppressed alleles are unaffected. Using a transient expression system in Nicotiana benthamiana, the LRR domain was identified as the domain conferring suppression. The results of this study suggest that the expression of closely related NB‐LRR resistance genes or alleles in the same genotype can lead to dominant‐negative interactions. These findings provide a molecular explanation for the frequently observed ineffectiveness of resistance genes introduced from the secondary gene pool into polyploid crop species and mark an important step in overcoming this limitation.